A Review on Synthesis, Properties, and Environmental Application of Fe-Based Perovskite - G. Jayanthi; Sowrirajan Sumathi; Karthik Kannan; V. Andal; Sivaraj Murugan (Advances in Materials Science and Engineering)
Perovskite has attracted the attention of researchers owing to its intriguing physicochemical properties and wide applications. Recently, Fe-based Perovskite as well as its nanoforms is an extensively studied material due to its photocatalytic activity, multiferroic properties, and chemical stability. Fe-based Perovskite exhibits a range of characteristics that become helpful for different applications such as catalysis, electrochemical sensors, and solar cells. This review summarizes the synthesis, properties, and environmental applications of Fe-based Perovskite. This review highlights and provides an overview of the transition metal substituent in Fe-based Perovskite and its properties and how it influences its application in wastewater treatment and catalysis. This article furnishes an overview on synthesis, properties, and environmental application of Fe-based Perovskite.